Feminist Poststructuralism and Discourse Analysis Revisited - Gavey, Nicola (Psychology of women quarterly, 2011)
In this article, the author tries to piece together the context in which she wrote "Feminist Poststructuralism and Discourse Analysis" (Gavey, 1989). The article grew out of her attempts to find a different way of doing psychology, after 8 or 9 years of studying and wrestling with the discipline. It is partly a personal story, but also a story about significant shifts in the production of knowledge that were taking place at the time. Looking back 21 years down the track, the author finds the basic gist of the feminist poststructuralist approach outlined in her original article still shapes how she looks at the world. There are ways in which she would have written the article differently now, and there are also points of unease or ambivalence, although not outright disagreement with what she wrote at the time. The invitation to revisit a paper written so long ago presents a privileged and deceptively challenging opportunity. The author ponders briefly on a few points that have come to mind in this process in terms of absent acknowledgements and points of unease as they related to current preoccupations.